PIM activity in tumours: A key node of therapy resistance. (January 2018) - Rebello, Richard J.; Huglo, Alisée V.; Furic, Luc
Abstract: The PIM kinases are proto-oncogenes which have been shown to facilitate cell survival and proliferation to drive malignancy and resistance post-therapy. They are able to suppress cell death signals, sustain PI3K/AKT/mTORC1 pathway activity and regulate the MYC oncogenic program. Recent work has revealed PIM kinase essentiality for advanced tumour maintenance and described tumour sensitivity to small molecule inhibitors targeting PIM kinase in multiple malignancies.